2016
DOI: 10.1155/2016/6972818
|View full text |Cite
|
Sign up to set email alerts
|

Planning the City Logistics Terminal Location by Applying the Greenp-Median Model and Type-2 Neurofuzzy Network

Abstract: The paper herein presents green p-median problem (GMP) which uses the adaptive type-2 neural network for the processing of environmental and sociological parameters including costs of logistics operators and demonstrates the influence of these parameters on planning the location for the city logistics terminal (CLT) within the discrete network. CLT shows direct effects on increment of traffic volume especially in urban areas, which further results in negative environmental effects such as air pollution and noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Formally, let n 5-9 be the number of residents in the microzone with an age in the range of 5-9 years, let n 10-14 be the number of residents in the microzone with an age in the range of 10-14 years, and let n [15][16][17][18][19] be the number of residents in the microzone with an age in the range of 15-19 years.…”
Section: Phase 1b-indicators and Fuzzy Rule Set Creationmentioning
confidence: 99%
See 2 more Smart Citations
“…Formally, let n 5-9 be the number of residents in the microzone with an age in the range of 5-9 years, let n 10-14 be the number of residents in the microzone with an age in the range of 10-14 years, and let n [15][16][17][18][19] be the number of residents in the microzone with an age in the range of 15-19 years.…”
Section: Phase 1b-indicators and Fuzzy Rule Set Creationmentioning
confidence: 99%
“…The indicator I 11 is given by the formula: I 11 = I 11a × n 5-9 + I 11b × n 10-14 + I 11c × n 15-19 n 5-9 +n 10-14 +n [15][16][17][18][19] (2)…”
Section: Phase 1b-indicators and Fuzzy Rule Set Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…Logistics prevention should be constantly adjusted to supported system requests; on the other hand, supported systems must be designed taking into account logistics prevention requests. Supported systems also need to adapt to the possibilities of logistics systems (Atanasković et al, 2009, pp.127-139), (Pamučar et al, 2016).…”
Section: Development Of the Logistics Prevention Conceptmentioning
confidence: 99%
“…FLS and ANFIS are widely used methods for solving various traffic engineering problems. Many authors gave the contribution in this field, and some of them can be found in the recently published papers [27,28]. For example, in paper [27] the authors describe the problem of choice of road route under conditions of uncertainty which the drivers face as they carry out their task of transportation.…”
Section: Introductionmentioning
confidence: 99%